Inequality and growth clubs (2005)
s the various chapters of this book make clear, coalition theory is extremely useful for microeconomic issues. But what about macroeconomics? If we adhere to the methodological program of modern macroeconomics to ground its research on explicit and firm microeconomic foundations, the answer is obviously yes. Actually, there are more precise reasons to think that coalitions matter for macroeconomic issues than the rather general and vague desire to build a bridge between microeconomics and macroeconomics: Institutions exist at the macroeconomic level that shape and organize the functioning of an economy. The clearest example of this is the modern central bank, which indirectly provides liquidities to the economy and plays a prudential role in the banking sector. But these institutions in turn are formed and not created by some deus ex machina. The creation of the European Monetary Union amounts to the formation of a coalition of countries willing to share monetary sovereignty, and the debates on the economic viability of the eurozone are de facto on the viability of this coalition. Public goods generating externalities on a wide scale, like education and public infrastructure, exist. But these goods depend on collective financing by a set of agents, be it a nation, a region or a neighborhood. More generally, externalities matter for macroeconomics, and they depend on the clusterings of agents and firms. There is such a diversity between agents that the representative agent hypothesis appears as a gross device that more and more macroeconomists tend to abandon. Recent macroeconomic models incorporate heterogeneity between agents and clusters within an economy.